Angiotensin I and II Stimulate Cell Invasion of SARS-CoV-2: Potential Mechanism via Inhibition of ACE2 Arm of RAS - Zorad, S; Skrabanova, M; Zilkova, M; Cente, M; Turic Csokova, N; Kovacech, B; Cizkova, D; Filipcik, P (Physiological research, 2024)
Angiotensin-converting enzyme 2 (ACE2), one of the key enzymes of the renin-angiotensin system (RAS), plays an important role in SARS-CoV-2 infection by functioning as a virus receptor. Angiotensin peptides Ang I and Ang II, the substrates of ACE2, can modulate the binding of SARS-CoV-2 Spike protein to the ACE2 receptor. In the present work, we found that co incubation of HEK-ACE2 and Vero E6 cells with the SARS-CoV-2 Spike pseudovirus (PVP) resulted in stimulation of the virus entry at low and high micromolar concentrations of Ang I and Ang II, respectively. The potency of Ang I and Ang II stimulation of virus entry corresponds to their binding affinity to ACE2 catalytic pocket with 10 times higher efficiency of Ang II. The Ang II induced mild increase of PVP infectivity at 20 microM; while at 100 microM the increase (129.74+/-3.99 %) was highly significant (p<0.001). Since the angiotensin peptides act in HEK ACE2 cells without the involvement of angiotensin type I receptors, we hypothesize that there is a steric interaction between the catalytic pocket of the ACE2 enzyme and the SARS-CoV-2 S1 binding domain. Oversaturation of the ACE2 with their angiotensin substrate might result in increased binding and entry of the SARS-CoV-2. In addition, the analysis of angiotensin peptides metabolism showed decreased ACE2 and increased ACE activity upon SARS-CoV-2 action. These effects should be taken into consideration in COVID-19 patients suffering from comorbidities such as the over-activated renin-angiotensin system as a mechanism potentially influencing the SARS-CoV-2 invasion into recipient cells.
Keywords: angiotensin I; angiotensin-konvertující enzym 2; inhibitory ACE; Angiotensin-Converting Enzyme 2; Angiotensin I; Angiotensin II; Peptidyl-Dipeptidase A; angiotensin II; Spike Glycoprotein, Coronavirus; lidé; Angiotensin-Converting Enzyme Inhibitors; angiotensin konvertující enzym; renin-angiotensin systém; Humans; glykoprotein S, koronavirus; Renin-Angiotensin System; COVID-19; SARS-CoV-2